Purchase order for the interior fit out work and supply of the allotted furniture on turn- key basis for the library of Brac University - Brac University (Brac University, 2023)
This purchase order has been made between Brac University and Synthesis Architects Ltd. for the interior fit out work and supply of the allotted furniture on turn- key basis for the library of Brac University.